Deep Cement Mixed Walls with Steel Inclusions for Excavation Support - Nishanthan, R.; Liyanapathirana, D.S.; Leo, C.J. (My University, 2018)
Deep cement mixed (DCM) walls are widely used in supporting excavations in many parts of the world. In this paper, a case study of an excavation supported by a DCM wall with steel inclusions is analysed using a three-dimensional finite element model and based on the coupled theory of nonlinear porous media. The DCM wall is constructed with wide flange steel inclusions. The stress–strain behaviour of the DCM wall section is simulated using an extended version of the Mohr– Coulomb model, which considers the strain-soften ing behaviour of DCM columns beyond yield. The computed lateral deformations are compared with the field measurements to validate the numerical modelling procedure. Using the same case study, the internal stability of the wall against bending and shear failure modes is investigated. In addition, the lateral pressure distribution along the wall length is investigated because in practice design is carried out considering a uniform pressure distribution assuming rigid wall movements. A parametric study was carried out to investigate the viability of DCM walls in supporting excavations by varying the spacing between steel inclusions, wall thickness
Keywords: Excavation support; Deep cement mixed columns; Steel inclusions; Finite element method; Strain softening; Ground movements